Posterior interosseous nerve palsy caused by synovial osteochondromatosis of the elbow analyzed by three-dimensional reconstruction: a case report - Koichi Yano; Yasunori Kaneshiro; Kosuke Sasaki; Hideki Sakanaka (Journal of Medical Case Reports, 2018)
Abstract Background Synovial osteochondromatosis, a benign tumor consisting of cartilage and bone, generally presents as multiple osteochondral or chondral nodules. Peripheral nerve palsy caused by synovial osteochondromatosis is rare. Three-dimensional reconstruction based on magnetic resonance imaging shows the specific shape and location of the tumor and its relation to the nerve. Case presentation We describe a case of posterior interosseous nerve palsy caused by synovial osteochondromatosis of the elbow in a 66-year-old Japanese man. A three-dimensional reconstructed image based on magnetic resonance imaging was used to determine the location and shape of the giant tumor, which was composed of bone and cartilage. After surgical resection of the giant tumor and neurolysis of the posterior interosseous nerve, he fully recovered from nerve palsy 9 months postoperatively. There was no recurrence of the lesion 1 year postoperatively. Conclusion Synovial osteochondromatosis that causes posterior interosseous nerve palsy has a characteristic morphology and location, that is, a giant tumor located anterior to the humeroradial joint, as revealed by three-dimensional magnetic resonance image reconstruction.